An Investigation Into Curved Layer Deposition for Fused Deposition Modelling - Raghu, Vivek Anand (Auckland University of Technology, 2010)
Rapid prototyping is a form of additive fabrication which is used to make three dimensional objects with shorter lead times. Fused Deposition modelling (FDM) is a type of Rapid prototyping, in which a semi solid plastic material is extruded layer by layer to build up a part. This is achieved by modelling of the desired part in 3D and converting this into 2D slices, which would be then readable by the machine and will hence build the part layer by layer. This type of fabrication is now being used in a number of applications from moulds for industrial components to reconstructing human body parts; however this type of manufacturing has not been widely accepted because of a number of limitations in the areas of – range of materials suitable, reduced output quality and strength, dimensional accuracy etc. The main barrier with this type of Rapid prototyping technology is that they are created by adding layers on top of one another. These create a lamination effect resulting in parts which are weak in strength. In addition there may be more issues like poor surface finish, large number of layers which may increase production time. A little of these shortfalls could be corrected if the material could be deposited in a curved fashion compared to the traditional flat layer deposition approach. Developing a curved layer deposition methodology can improve part quality by reduced lamination, reduction in the staircase effect which leads to improved dimensional accuracy of the part and improved strength due to better bonding and continuity between layers. The main aim of this project is to create a new type of rapid prototyping in which the layers of material which make up the part can be deposited in curved layers. This will help in the direct production of parts of curved and complicated shapes and sizes. This in turn will enable in an improvement in the production times of the parts manufactured as flat layers, better product strength, and improved overall surface quality. This is achieved by doing preliminary research and investigation into the concept of curved layer fused deposition modelling (CLFDM), studying the work done on this field till date, analyzing the shortcomings and develop a working methodology to print simple curved parts. These curved parts can then be tested for their varied properties and compared to the same parts printed as flat layers. This project involves in the design and development of a test bed based on the Fab@Home machine around which this whole project is based. In order to print the sample parts, they are modelled as per the desired shape and requirement. This model is then converted into a format which mainly contains all the points through the body of the model. This file is then given into a curved slicing algorithm which generates the slicing procedure readable by the fab@home machine which will then be used in printing the physical part initiating the curved layer deposition process.